Promoting social learning in the Swedish leisure time centre. Issue 3 (3rd July 2019) - Jonsson, Kristina; Lillvist, Anne
ABSTRACT: Swedish leisure time centres (LTCs) are included in the Swedish Education Act and are used by almost every pupil in the age range of 6–9 years. They are governed by national policy documents with a certain emphasis on social learning. This article aims to highlight the LTC staff's perspectives on their work of promoting social learning in the Swedish LTC. The article is based on a qualitative study, with data from group interviews with 21 LTC staff. The data are analysed with an abductive approach, with Bronfenbrenner's bioecological systems theory as a theoretical point of departure. Our results show that the work is directed both by the staff's beliefs and by the structural conditions of the activities, which the staff seldom feel able to influence. This causes frustration among staff and, owing to a lack of didactic reflections, social learning among pupils is not optimised. We argue that the LTC needs to be further explored, at the municipal and local management levels, to enable optimised social learning for pupils in the LTC.